Teaching economics outside one's own subject area at lower secondary level in Austria – enriching or embarrassing? - Fridrich, Christian (JSSE - Journal of Social Science Education, 2021)
Purpose: This paper will examine the extent to which Economics education within the integrated Austrian subject of Geography and Economics delivered by teachers outside their own subject area differs from teaching delivered by those with a formal qualification in the subject. Design: Hypothesis testing was carried out using variance analyses, factor analyses and χ² independence tests; qualitative content analysis was used to evaluate responses to the open questions of a questionnaire (Mayring 2000, Kuckartz 2012). Findings: The results show significant differences between the two teacher groups with regard to the popularity of Economics education, attitudes towards economics generally, and professional self-image. Limitations and implications: For resource reasons, the study had to be limited to Vienna. A further broader investigation seems necessary. Practical implications: In order to support teachers working outside their own subject area, two project networks have